Pemberdayaan Wirausaha Melalui Rancangan Ekosistem Bisnis Berbasis Platform Digital - Martanto; Mulyawan; Arif Budi Setiawan; Betran Renaldi (CV. Multi Kreasi Media, 2024)
Micro, small, and medium enterprises (MSMEs) play a vital role in the economy but often face challenges in developing their businesses in the digital era. This Community Partnership Program aims to empower entrepreneurs through the design of a business ecosystem based on digital platforms. The activities include situational analysis of partner MSMEs, designing a suitable business ecosystem model, training on the utilization of digital platforms for various business aspects (marketing, operations, and management), and assistance in implementing the designed ecosystem. It is expected that, through this program, partner MSMEs can improve efficiency, expand market reach, enhance customer interaction, and ultimately achieve sustainable business growth through the utilization of an integrated digital ecosystem.